Racial and ethnic disparities in adverse birth outcomes: Differences by racial residential segregation - Renee Mehra; Danya E. Keene; Trace S. Kershaw; Jeannette R. Ickovics; Joshua L. Warren (Elsevier, 2019)
Racial and ethnic disparities in adverse birth outcomes have persistently been wide and may be explained by individual and area-level factors. Our primary objective was to determine if county-level black-white segregation modified the association between maternal race/ethnicity and adverse birth outcomes using birth records from the National Center for Health Statistics (2012). Based on maternal residence at birth, county-level black-white racial residential segregation was calculated along five dimensions of segregation: evenness, exposure, concentration, centralization, and clustering. We conducted a two-stage analysis: (1) county-specific logistic regression to determine whether maternal race and ethnicity were associated with preterm birth and term low birth weight; and (2) Bayesian meta-analyses to determine if segregation moderated these associations. We found greater black-white and Hispanic-white disparities in preterm birth in racially isolated counties (exposure) relative to non-isolated counties. We found reduced Hispanic-white disparities in term low birth weight in racially concentrated and centralized counties relative to non-segregated counties. Area-level poverty explained most of the moderating effect of segregation on disparities in adverse birth outcomes, suggesting that area-level poverty is a mediator of these associations. Segregation appears to modify racial/ethnic disparities in adverse birth outcomes. Therefore, policy interventions that reduce black-white racial isolation, or buffer the poor social and economic correlates of segregation, may help to reduce disparities in preterm birth and term low birth weight. Keywords: Bayesian meta-analysis, Health disparities, Preterm birth, Racial residential segregation, Term low birth weight